Kampanye Moderasi Beragama di Ruang Digital Indonesia - Robeet Thadi (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Religious moderation is a trending conversation in the digital space, this article aims to explain the concept of religious moderation, religious topics, forms of campaigns, and strategies for campaigning for religious moderation in Indonesia's digital space. This article uses a qualitative approach to the liberary research method. The results of the study show that, in terms of the concept of moderation, religion is a middle attitude, not secular and not religious. The religious topic of religious moderation from the Google search engine page uses the keywords "Religious Moderation" (over 3.4 million), "Islamic Moderation" (over 3.7 million) higher "wasathiyah" (over 182 thousand), while "Moderation" (5.7 million). Through google trends the results of searching for religious moderation (32%), Islamic moderation (5%) wasathiyyah (less 1%), while moderation (48%), in the form of religious moderation messages can be conveyed in the form of posters, banners, billboards, speeches, and discussion ad. Meanwhile, the campaign strategy for religious moderation by presenting Islam as a humanist religion, changing the paradigm from qabilah to ummah, revitalizing kaffah Islam.